Preparation of a hybrids APT@MIL by one-step solvent-thermal method for effectively degrading organics - Yaping Zhang (IWA Publishing, 2021)
The attapulgite (APT), a typical nano-rod structured clay was introduced to MIL-101(Fe), a typical eco-friendly iron-based Metal-Organic Framework material (MOF), during the preparation by a one-step solvothermal method, which afforded a novel APT and MOF hybrid (APT@MIL). Based on the characterization of SEM, FT-IR and XRD, it was found that the rod-like crystals of APT determined the size of MIL-101(Fe) while maintaining its regular octahedral crystal form, and the crystal size of MIL-101(Fe) in APT@MIL enlarged 4 times. It was also discovered that the rod-like APT were evenly distributed in MIL-101(Fe) crystals. Using APT@MIL as the photocatalyst, some organic dyes were photodegraded in simulated sunlight. The analysis indicated that APT@MIL has high adsorption and photodegradation activity, the removal rate of methylene blue was up to 99.5%. Finally, the photocatalytic activity of APT@MIL was verified by UV-Vis DRS, photoluminescence spectra. The thermodynamic adsorption, kinetic characteristics adsorption, and removal mechanism of APT@MIL are also discussed. In summary, a novel hybrid material APT@MIL was successfully prepared with good adsorption and photocatalytic performance. It is expected to be used in photocatalytic degradation of dye wastewater.